EFEKTIVITAS DEEP BREATHING TERHADAP KECEMASAN IBU HAMIL DENGAN PLASENTA PREVIA : EVIDENCE BASED CASE REPORT (Politeknik Kesehatan Kemenkes Bandung, 2022)
Anxiety in pregnant women in the third trimester is caused by unpleasant emotional states. The level of anxiety known greatly affects the welfare of pregnant women and fetuses in the womb. Low levels of anxiety in pregnant woman can reduce complications caused by pregnancy. The purpose of this Evidence Based Case Report is to find out the effectiveness of Deep Breathing therapy in overcoming anxiety in pregnant women with placenta previa. The method in this EBCR was using the Google Scholar database, PubMed, Chocrane and scopus. The results were limited to only original article and published from 2011-2021. According to the inclusion criteria and exclusion criteria there were three journals that can be used in accordance with the purpose of this Evidence Based Case Report. The full texts were obtained and critically reviewed using 3 aspects, namely the validity, the importancy, and applicability or relevance to existing clinical problems. The results showed the articles were valid, important and applicable with the level of evidence IIA and IIB. Based on the application of this EBCR in this case, the cause of anxiety was traced and the deep breathing technique was applied according to the needs consequently reduce the anxiety. Deep breathing technique therapy can be done as much as 3 times a day and anxiety levels reassessed after 6 days.